Correlation between Elementary School Students’ Mathematics Self-Efficacy and Motivation - Mulyani, Eva Astuti; S, Annisa Kasdiyanti; Ain, Siti Quratul; Alim, Jesi Alexander (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2020)
This research aims to determine the positive and significant correlation between mathematics self- efficacy and motivation of elementary school students. This type of research is quantitative using the correlation method. The population of this research was all fifth grade students of Elementary School in Cluster I of Marpoyan Damai District in Pekanbaru, which totaled 705 students. The research sample consisted of 183 students who were selected using cluster techniques. Data collection was carried out using a mathematics self-efficacy questionnaire and a motivation questionnaire and documentation, and the hypothesis was tested using the product moment correlation test and t test. The results showed that there was a positive correlation between mathematics self-efficacy and motivation of fifth grade elementary school students, indicated by a correlation coefficient of 0.353 with a fairly strong relationship category, and there was a significant correlation between mathematics self-efficacy and motivation of fifth grade elementary school students, as seen from the tcount = 5.078, greater than ttable = 1.653, at a significance of 5%. The contribution made mathematics self-efficacy to motivation is equal to 12.5%.